POLITICAL AND JUDICIAL RIGHTS OF NON-MUSLIMS IN MUSLIM STATES: A NORMATIVE AND HISTORICAL STUDY - Nurwidyani, Intan Meurduati; Siti Nazla Raihana (Al-Majaalis : Jurnal Dirasat Islamiyah, 2025)
This study explores the political and judicial rights of non-Muslims in Muslim-majority countries, focusing on their categorization, rights, obligations, and limitations as discussed by Islamic scholars. The findings reveal that non-Muslims, particularly ahl al-dhimmah, enjoy significant civil protections, religious freedoms, and the right to maintain their own judicial systems for personal matters. However, certain restrictions exist, such as the obligation to pay jizyah and limitations on holding primary leadership positions, which serve to preserve the social, ideological, and legal order of the Islamic state. The study demonstrates that Islam balances minority rights with the moral and political framework of governance, providing a nuanced understanding of coexistence in historical and contemporary Muslim societies.